Gait characteristics in idiopathic normal pressure hydrocephalus: A controlled study using an inertial sensor system - Johanna Rydja; Petra Pohl; Andreas Eleftheriou; Fredrik Lundin (PLoS ONE, 2025)
Background Gait disturbance is the most pronounced symptom in idiopathic normal pressure hydrocephalus (iNPH). Some gait parameters have been previously described, but an in-depth description of the gait pattern is lacking. The aim was to quantitatively evaluate gait in iNPH patients before and after shunt surgery and compare it to healthy individuals (HI), and correlate it with functional tests preoperatively. Methods In total, 47 patients and 42 HI were included. The patients were assessed with the iNPH scale (total, gait and balance domain scores were analyzed), the timed up and go test (TUG) and an inertial sensor gait analysis system, RehaGait®, pre- and postoperatively. The HI were assessed with TUG and RehaGait®. Gait variables were: stride length, stride duration, velocity, cadence, variability, stance, swing, single support, double support, step height, hip, knee and ankle joint angles. Results Compared to HI, the main differences in the gait variables were: decreased stride length (p < 0.01), velocity (p < 0.01), swing time (p < 0.01), single support (p < 0.01), hip flexion (p < 0.01), heel strike angle (p < 0.01) and toe-off angle (p < 0.01). Step height was normalized postoperatively; all other variables remained significantly worse than the HI. There were strong correlations between stride length, velocity, heel strike angle, and toe-off angle and the functional gait tests, but no correlations for any variable and the balance domain score. Conclusions The patients walked with reduced hip flexion, heel strike angle and toe-off angle, and had shorter strides, decreased velocity, and increased time for swing and single support, compared to HI. Step height was the only gait variable normalized after shunt surgery. Ankle joint kinematics correlated strongly with the results in functional gait tests. More research is warranted about how gait speed affects other gait variables in iNPH. Trial registration ClinicalTrials.gov NCT04795089